Real-World Impact of Switching From Insulin Glargine (Lantus®) to Basaglar® and Potential Cost Saving in a Large Public Healthcare System in Saudi Arabia - AlRuthia, Yazed; Bahari, Ohud H.; Alghnam, Suliman; Alrumaih, Ali M.; Asiri, Hassan; Alshammari, Mohammed; Alhowimel, Mansour; Al-Abdulkarim, Hana A. (Frontiers in Public Health, 2022)
Background: The advent of Basaglar®, which is a biosimilar insulin glargine formulation for Lantus® has brought hope that it will result in similar outcomes and lower costs. However, some health practitioners raised some concerns about the therapeutic equivalence of this new biosimilar. Therefore, we aimed to examine the clinical and financial impact of substituting Lantus® with Basaglar®. Methods: This was a retrospective chart review study in which adult patients (e.g., ≥18 years) with diabetes mellitus (DM) who were treated with insulin glargine (Lantus®) for at least 12 months, and then were switched to Basaglar® and treated for 12 months were retrieved from the electronic healthcare records of a large public healthcare system in Saudi Arabia. The potential cost savings for the years of 2018 to 2021 and cost avoidance for 2022 were estimated using different substitution ratios between the two insulin glargine products (Basaglar® and Lantus®) and acquisition prices. Results: One-hundred patients with DM who were previously treated with Lantus® and switched to Basaglar® were retrospectively recruited. About two-thirds of the patients (68%) had type 2 DM, and male and female patients were equally represented with a mean A1C of 9. The mean difference in the A1C levels before and after switching to Basaglar® was not significant (0.18, P-value=0.503, 95% CI [-0.36–0.72]). Although no statistically significant difference in the total daily insulin units between Lantus® and Basaglar®, the difference was leaning toward significance despite the small sample size (-1.88, P-value=0.25, 95% CI [-5.15–1.38]). Substituting Lantus® with Basaglar® could have led to significant cost savings which could have ranged from approximately 1.77 to 23.7 million United States Dollars (USD) for the years of 2018 to 2021 assuming an equal conversion ratio. However, these cost savings might not be realized if the switching to Basaglar® required higher daily insulin units, and the difference in the public tender acquisition price between Lantus® and Basaglar® was less than 15%. Conclusion: Basaglar® and potentially other biosimilar insulin glargine products can lead to significant cost savings without compromising the quality of care; however, their acquisition prices should be discounted.